A new cyclobutane substituted Schiff base ligand, synthesis of its Cd(II), Co(II), Cu(II), Ni(II) and Zn(II) complexes and investigation of their structure - Çukurovali, A; Yilmaz, I (Gordon Breach Publishing, Taylor & Francis Group, 2001)
A new, thiazole derivative ligand, 4-(1-phenyl-1-methylcyclobutane-3-yl)-2-(2-hydroxy-5-bromo benzylidenehydrazino) thiazole (LH), has been synthesized by the reaction of 2-hydroxy-5-bromobenzaldehyde, thiosemicarbazide and subsequently 1-phenyl-1-methyl-3-(2-chloro-1-oxoethyl) cyclobutane. Mononuclear complexes with a metal-ligand ratio of 1:2 have been prepared with Cd(II), Co(II), Cu(II), Ni(II) and Zn(II). The authenticity of the ligand and its complexes was established by elemental analyses, IR, C-13 and H-1 NMR spectra, magnetic susceptibility measurements and thermogravimetric analyses (TGA) and differential scanning calorimetry (DSC).
Keywords: cyclobutane; thiazole; Schiff bases; Schiff base complexes